2003
DOI: 10.1161/01.str.0000046456.26587.8b
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Measurement of Fluid-Induced Wall Shear Stress in Unruptured Cerebral Aneurysms Harboring Blebs

Abstract: Background and Purpose-Little attention has been focused on the role of fluid-induced wall shear stress in fully developed cerebral aneurysms. The purpose of this study is to evaluate the alternation and distribution of wall shear stress over 1 cardiac cycle in patients' aneurysms. Methods-A middle cerebral artery aneurysm and a basilar tip aneurysm with localized outpouching (blebs) in their domes were selected for this study. With the use of a stereo lithography machine, geometrically realistic aneurysm mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 38 publications
3
72
1
1
Order By: Relevance
“…The bleb at the tip of aneurysm 3 developed away from the inflow jet in a region of low WSS. This is in contrast to the results of Tateshima et al, 20 who found that the aneurysmal dome blebs were exposed to higher fluid-induced shear stress than any other measured points on the aneurysmal wall. Cebral et al 21 observed that in 1 of 7 aneurysms studied, bleb formation occurred in a region of low WSS associated with the outflow zone.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The bleb at the tip of aneurysm 3 developed away from the inflow jet in a region of low WSS. This is in contrast to the results of Tateshima et al, 20 who found that the aneurysmal dome blebs were exposed to higher fluid-induced shear stress than any other measured points on the aneurysmal wall. Cebral et al 21 observed that in 1 of 7 aneurysms studied, bleb formation occurred in a region of low WSS associated with the outflow zone.…”
Section: Discussioncontrasting
confidence: 99%
“…29 The WSS is sensed by various mechanosensors on/within the EC and is transduced into chemical signals that activate signaling pathways within the EC, which control its functionality 30 and the functionality of the artery. The molecular mechanism of action for WSS with regard to the growth and rupture of cerebral aneurysms is still unknown, 31 and as such, there are competing hypotheses: High WSS is related to the initiation of cerebral aneurysm formation 20 and low WSS, to the continual enlargement, and possibly rupture, of cerebral aneurysms by causing degenerative changes in the wall. 32 A combination of high WSS and a high WSS gradient may represent a dangerous hemodynamic condition that predisposes to aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the role of hemodynamics in cerebral aneurysm degeneration, it is necessary to analyze the intra-aneurysmal flow, based on clinical images. Tateshima et al 3 identified the significance of intra-aneurysmal flow obtained with a realistic vascular model of a basilar tip aneurysm, and they highlighted the significance of WSS affecting the aneurysmal wall. Ujie et al 4 reported a recirculating flow pattern in ruptured aneurysms and proposed that the presence of a recirculation region may be related to an increased risk of aneurysm rupture.…”
mentioning
confidence: 99%
“…Tateshima et al measured and evaluated the alternation and distribution of WSS in two aneurysm models (middle cerebral artery and basilar tip, both with blebs at their domes). They noticed that both aneurysm models blebs were exposed to high WSS, region where the arterial wall is the finest in vivo [26]. Hollnagel et al used LDV to validate phase-contrast magnetic resonance angiography (PC-MRA) in a patient specific aneurysm model under steady flow conditions.…”
Section: Laser Doppler Velocimetry (Ldv)mentioning
confidence: 99%